Inhibition of human macrophage colony formation by interleukin 4 (The Rockefeller University Press, 1989)
We investigated the effects of human rIL-4 on in vitro hematopoiesis. A profound inhibition of macrophage colony formation by IL-4 was observed, whereas colony growth of other lineages was not affected. Inhibition of macrophage colony growth was not restricted to GM-CSF- induced colony growth but was also present in cultures stimulated with M-CSF. This inhibition was not only observed in cultures of light density bone marrow cells, but also in cultures of monocyte- and T lymphocyte-depleted bone marrow cells. Since a similar inhibition was observed in cultures of CD34+HLA-DR+-enriched bone marrow cells, a direct action of IL-4 on monocyte-committed progenitor cells is suggested.